Design improvement of coffee maker using design for assembly (DFA) method - Mohd Raz Firdaus, Ramli (2012)
Nowadays companies especially manufacturer trying to cut down the manufacturing cost by improved and adjusted the manufacturing process and assembly method and at the same time increase their profit. In order to be a competent player in the market, the product should arrive into market within a short time and reasonable price. This study basically shows a detailed study to improve the design of Coffee Maker by using Design for Assembly and also studies the assembly efficiency using Boothroyd Dewhurst Design for Assembly (DFA) method. Assembly cost is one of the major operations in manufacturing but always ignored during designing stage. In this study, comparative analysis was done between current and alternative design. The design was done by using CATIA software and analysed by using manual and DFA software analysis to get the efficiency of current design. By applying Boothroyd Dewhurst DFA method guideline, alternative design was generated and analysed using the same method to compare the effectiveness of this new alternative design focuses on part that has been identified for improvement. From the result, it was found that the assembly cost was decreased from 117.49 second into 92.59 second after reduction from 14 parts into 11 parts. It was proven that this Boothroyd Dewhurst DFA method was able to improve the design in terms of design efficiency where the current design efficiency is 5.1% and for proposed design the efficiency became 6.3%. This method can be applied in manufacturing company in order to improve their design effectiveness.